Sonneratia alba sebagai Sumber Senyawa Antibakteri Potensial - Herawati, Netti; Jalaluddin, Noor; Daha, La; Zenta, Firdaus (Indonesia Chimica Acta, 2009)
Four different organic solvents, methanol, N- heksana, kloroform, and etil acetate were used to extracted some bioactive compounds from bark of mangroves plant Sonneratia alba (kayu buli) for screening of antibacterial activity against three pathogen bacteria, Staphylococcus aureus,Eschericha coli, and Bacillus subtillis by agar diffusion method. All extracts were able to inhibit the growth of these bacterial significantly in concentration of 5%. Etil acetate ekstract showed highest antibacterial activity.Methanol, chloroform, and etil acetate were effective solvent to extract bioactive compound that have a antibacterial properties from this plant.Keyword: Kayu buli, Sonneratia alba, antibacterial activity